Pengaruh Promosi jabatan dan Stres Kerja Terhadap Kinerja Karyawan pada PT. Mega Lestari Pratama Medan - Febrilian Lestario (CERED Indonesia Institute, 2021)
The purpose of this study was to examine and analyze the effect of job promotion and job stress on employee performance at PT Mega Lestari Pratama Medan. This research uses associative quantitative data analysis method, multiple regression analysis with t-test (partial test), F test (simultaneous test) and coefficient of determination test (R2). The test equipment of this research used multiple linear regression model. The results of the research simultaneously prove that job promotion and job stress affect employee performance. The results of the research partially prove that promotion has an effect on employee performance with a dominant influence. The results of the partial test also prove that work stress has an effect on employee performance.